Mandatory governance reform and corporate risk management - Hege, Ulrich; Hutson, Elaine; Laing, Elaine (Journal of Corporate Finance, 2021)
Using the Sarbanes-Oxley Act of 2002 as a quasi-natural experiment to identify the impact of corporate governance reform on foreign exchange risk hedging, we find that the substantial improvements in governance standards increased derivatives hedging and reduced foreign exchange exposure. The results are robust whether we consider initial reform gap or actual implementation, focus on legally required governance measures or include voluntary concomitant reforms. The economic magnitude of the effect is large. Our findings are corroborated by cross-sectional evidence, showing that firms with larger foreign markets exposure and a larger distortion in CEO incentives react more strongly to the reform. Financial hedges are implemented rapidly whereas exposure measures that encompass operational hedges take more time to adjust.